Improving student learning activities in microbiology through lesson study activities. Issue 1 (January 2021) - Irwandi, I; Hasan, R
Abstract: Lesson study is an educator development program through collaborative and continuous learning based on the principles of collegiality. Lesson study can be implemented at various levels of education from primary schools to universities. The 4 cycles-lesson study presented here is aimed to improve students' learning activities in microbiology subject in the Biology Education Department, Universitas Muhammadiyah Bengkulu. Students who engaged in this activity as much as 28 students. The lesson study activities were conducted in three stages: plan (plan), implementation (do) and reflection (see). Selected topics in this activity were infection and viruses. In addition to those topics, a practical class for (1) preparation of microorganism culture media and its sterilization; and (2) the proliferation of fungi and bacteria was also accomplished. The results showed that there is an improvement in the students learning activity by conducting a lesson study program on a microbiology course. The obtained results prove that lesson study can improve lecturer professionalism. This improvement in lecturer professionalism then will have an impact on the effectiveness of learning activities and on improving the quality of education overall.